2.9k views
1 vote
2.5 ( 6 x - 4 ) = 10 + 4 ( 1.5 + 0.5 x )

User Scottalan
by
4.2k points

1 Answer

6 votes

Answer:


\bold{x=2}

Step By Step Explanation:

Expand
\bold{2.5\left(6x-4\right): \ 15x-10}

Expand
\bold{10+4\left(1.5+0.5x\right): \ 2x+16}


\bold{15x-10=2x+16}

Add 10 To Both Sides


\bold{15x-10+10=2x+16+10}

Simplify


\bold{15x=2x+26}

Subtract 2x From Both Sides


\bold{15x-2x=2x+26-2x}

Simplify


\bold{13x=26}

Divide Both Sides By 13


\bold{(13x)/(13)=(26)/(13)}

Simplify


\bold{x=2}

User PsychoX
by
5.1k points